BASIC PRINCIPLES AND CONCEPTS UNDERLYING RECENT ADVANCES IN MRI OF THE DEVELOPING BRAIN - Panigrahy, Ashok (2010)
Over the last decade, magnetic resonance imaging has become an essential tool in the evaluation of both in vivo human brain development and perinatal brain injury. Recent technology including MR compatible neonatal incubators, neonatal head coils, advanced MR pulse sequences and 3T field strength magnets allow high quality MR imaging studies to be performed on sick neonates. This article will review basic principles and concepts underlying recent advances in MR spectroscopy, diffusion, perfusion and volumetric MR imaging. These techniques provide quantitative assessment and novel insight of both brain development and brain injury in the immature brain. Knowledge of normal developmental changes in quantitative MR values is also essential to interpret pathologic cases.